Structural relations of illness perception, fatigue, locus of control, self-efficacy, and coping strategies in patients with multiple sclerosis: a cross-sectional study - Amir Akbari Esfahani; Abbas Pourshahbaz; Behrooz Dolatshahi (BMC, 2024)
Abstract Background Patients with multiple sclerosis (MS) experience extensive problems due to fatigue and illness perception. Reducing these problems may improve these patients' quality of life (QoL). Accordingly, the current study is aimed at investigating the mediating role of self-efficacy, locus of control, coping strategy, and outcome expectancy in the relationship between illness perception and fatigue severity in patients with MS. Methods In a cross-sectional analytical study, data of 172 MS patients were collected by self-report questionnaires including illness perception questionnaires (IPQ-R), Multiple Sclerosis Self-Efficacy (MSSES) scale, health locus of control (MHLC), coping strategies in MS(CMSS), outcome expectancy, level of physical activity (IPAQ-SF), patient activation measure (PAM-13) and fatigue severity scale (FSS). The data were analyzed using linear and multiple regression analysis in SPSS software version 24 (SPSS Inc., Chicago, IL, USA). Results The final model explained 62% of the fatigue variance. Illness perception both directly and indirectly (through self-efficacy, physical activity level, internal health locus of control, patient activation, and negative coping strategies) could predict the participants' fatigue severity. Among the mediating variables, internal health locus of control, self-efficacy, and negative coping strategies had the greatest impact, respectively. moreover, outcome expectancy variable did not a mediating role in the aforementioned relationship. Conclusions To enhance the well-being of MS patients and to improve the efficiency of treating MS related fatigue, a comprehensive treatment protocol is needed, encompassing psychological factors affecting fatigue severity.